Do Perceived Security and Financial Literacy Affect the Use of Financial Technology? - Febrianti, Fatimah; Sabandi, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
The purpose of this study is to demonstrate the variables that affect college students’ use of financial technology (Fintech). The use of fintech in financial transactions is an interesting topic to discuss, but previous research in this topic is still debatable, so further study is needed. This research adopts the Technology Acceptance Model (TAM) theory. This study is a quantitative research with a research sample of 397 out of 45,713 population of Sebelas Maret University students taken by purposive sampling technique. Collecting data with a google forms questionnaire. The data analysis technique uses instrument validity and reliability tests, multicollinearity test, goodness of fit test, and Hierarchical Regression Analysis with SmartPLS software. The study's findings suggest that perceived security and financial literacy positively and significantly influence perceived usefulness; perceived security and financial literacy positively and significantly influence perceived ease of use; perceived security, financial literacy, perceived usefulness, and perceived ease of use positively and significantly influence the use of fintech. In addition, perceived usefulness and ease of use partially mediate the relationship between perceived security and financial literacy on fintech usage. This research helps Fintech service providers to improve fintech security and encourages students to improve financial literacy.